Hubungan Pancasila dengan Pembukaan UUD 1945 the Relationship Between Pancasila and the Opening of the 1945 Constitution - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Adabi Dino Sweta; Riris Rahmadani Putri Utomo; Dinta Rizqi Aulia Febriani; Siwi Budi Utami (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The foundation of the Indonesian nation is Pancasila. In Indonesia, the 1945 Constitution serves as the foundation. As an example of a country that has adopted Pancasila as its national anthem, Indonesia is one such country. As an ideology, personal code of ethics, and economic foundation of the Indonesian nation, Pancasila has been assimilated into the guiding principles of the Indonesian nation. The Republic of Indonesia, which was founded on August 17, 1945, is officially known as Pancasila, a name taken from the Arabic letter 0 (Slaat). The Indonesian government designed Pancasila and the Preparatory Party for Indonesian Independence approved it. At the 1945 Session of the People's Representative Council of the Republic of Indonesia, Pancasila was ratified. As the foundation of the state and the foundation of the life of the Indonesian people, the practice of the values ​​of Pancasila is an obligation for all Indonesian people. As a value that can be applied by society in Pancasila. On the other hand, the 1945 Constitution establishes a clear basis for legislative action. Both Pancasila as a national principle and the 1945 Constitution, especially the prohibition clause, as a legal principle, have a very close or inseparable relationship. If Pancasila is hereditary, then the 1945 Constitution is also hereditary. In other words, everything in the government's power structure - including laws, decisions, the executive branch, the democratic system, and so on - must be in accordance with the values ​​outlined in Pancasila. Therefore, the relationship between Pancasila and the 1945 Constitution is a formal relationship. In other words, Pancasila is a positive standard and guiding principle for national development. Pancasila is a strong and unchangeable concept. On the other hand, the creation of the 1945 Constitution is considered the highest decision. In addition, there is a material relationship between Pancasila and the 1945 Proclamation Constitution. Thus, the 1945 Constitution is the basic document of Indonesian law, with all its provisions and clauses derived from Pancasila.